Determining concrete fracture parameters using three-point bending beams with various specimen spans. (June 2020) - Yin, Yangyang; Qiao, Yanmin; Hu, Shaowei
Highlights: The effects of specimen spans on concrete fracture parameters were revealed. With the increase of span-depth ratio, the critical effective crack length increased linearly. The applicability of the proposed linear interpolation method was verified by the available methods in literatures. Abstract: The effects of specimen spans on concrete fracture parameters were firstly investigated using three-point bending beams. The calculation formulae of the fracture parameters for specimens with span-depth ratios commonly used in testing were put forward based on linear interpolation method. Six span-depth ratios (2, 2.5, 3, 4, 5 and 6) for concrete specimens were explored. Results show that (1) with the increase of span-depth ratio, the critical effective crack length increased linearly whilst constant initial and unstable fracture toughness were obtained; (2) furthermore, the applicability of the proposed linear interpolation method was verified by the available methods in literatures.